2015
DOI: 10.11648/j.ajce.20150305.12
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Physical Properties of Local Materials Used in the Construction of Chad

Abstract: As earth is the most commonly used construction material in Chad, the purpose of the present study is to characterize it as a whole, and to characterize its thermo physical properties. Various tests were conducted on it and mainly on its thermo-physical characteristics, as these significantly affect the comfort of a house. The study focused on earth taken from a climate zone of Chad, mixed with straw at a given proportion or used alone. Different values of thermal conductivity and diffusivity of these material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…They therefore involved in the heat balance of the volume of air inside the thermal zone studied. These expenses are mainly due to occupants, machines and lighting are considered according to Figure 4 [10].…”
Section: Creating Internal Loadsmentioning
confidence: 99%
See 1 more Smart Citation
“…They therefore involved in the heat balance of the volume of air inside the thermal zone studied. These expenses are mainly due to occupants, machines and lighting are considered according to Figure 4 [10].…”
Section: Creating Internal Loadsmentioning
confidence: 99%
“…Fanger proposed formulas for calculating each of the speaker terms in equation (10) the thermal balance of the body in a state of thermal comfort. These formulas were derived from experimental studies involving a large number of subjects (1300) and include both physical and physiological measurements and the record subjective assessments of the test subjects.…”
Section: The Model Of Fangermentioning
confidence: 99%
“…The earth used in building is either fired or raw, but in most cases reinforced with fibrous materials of plant origin such as straw, hemp and agricultural waste [4,5,6,7]. However, many researchers have studied the thermophysical characteristics of these composite materials and have shown that they have sufficient mechanical strength and also very high thermal insulation properties [8,9,10,11]. Studies have also carried out on stabilised earth with a small percentage of cement [1,2,8].…”
Section: Introductionmentioning
confidence: 99%